A passion for faithfulness wisdom from the book of Nehemiah - Packer, James Innell, 1926- (Wheaton, IL Crossway, 1995)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. Nehemiah -- criticism, interpretation, etc